Effective adsorption of diclofenac and naproxen from water using fixed-bed column loaded with composite of heavy sugarcane ash and polyethylene terephthalate - Américo-Pinheiro, Juliana Heloisa Pinê [UNESP] (2022)
The contamination of water by pharmaceutical pollutants is a major issue these days due to excessive use of these ingredients in modern life. This study evaluated the adsorption and effectiveness of a low-cost composite prepared from heavy sugarcane ash (HSA) fused with polyethylene terephthalate (PET) and functionalized with iron (Fe3+) in a dynamic system through a fixed-bed column. The solution of synthetic drugs was prepared and placed in a reservoir, using a peristaltic pump the solution is run onto the fixed bed column at a flow rate of 2 mL min−1. Saturation time and adsorption capacity were evaluated by centrifugation and extraction after a regular interval of 2 h from the adsorption column. The samples were analyzed using high-performance liquid chromatography (HPLC) and the data was modeled for quantification. For DIC removal, an adsorption capacity of 324.34 μg. g−1 and a saturation time of 22 h were observed, while the adsorption capacity of NAP was 956.49 μg. g−1, with a saturation time of 8 h. Thus, the PETSCA/Fe3+ adsorbent proved to be quite efficient for removing the pharmaceutical pollutants, with a longer period of operation for DIC removal. These findings suggested that a highly efficient bed column made from a less expensive waste material and could be used to remove hazardous pharmaceutical contaminants.